PENGARUH PROMOSI DAN HARGA TERHADAP MINAT BELI KONSUMEN PADA TOKO SEPATU BATA MTC GIANT PEKANBARU - Tondang, Berty Windi; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
MTC Giant Panam Pekanbaru brick shoe store is a company engaged in the field of shoes products. In order to face increasingly difficult competition, a company must pay attention to promotions and prices in order to attract buying interest from consumers. For this reason, this research was conducted, research with the promotion variable (X1) and Price (X2) and the dependent variable, namely Consumer Purchase Interest (Y). The problem in this research is that buying interest in shoe shops has fluctuated and tends to decrease every year.This study aims to determine, and can explain the effect of promotion and price on consumer buying interest in the MTC Giant Panam Pekanbaru Pekanbaru. The sample of this study was taken as many as 100 respondents from the entire population and calculated using the Slovin formula, where the method used in collecting questionnaires was the accidental sampling method. And data collection techniques used are questionnaires and interviews, while the data analysis techniques used are simple linear regression and multiple linear regression.From the results of research conducted, that the effect of promotion on prices has a significant effect, and prices also influence buying interest significantly, so does Promotion and Prices also have a significant effect on consumer buying interest. Keywords: Promotion,Price, and Customer Buying Interest